Association of 25-hydroxyvitamin D with type 2 diabetes among patients undergoing coronary angiography: cross-sectional findings from the LUdwigshafen Risk and Cardiovascular Health (LURIC) Study - Ó Hartaigh, Bríain; Thomas, G. Neil; Silbernagel, Günther; Bosch, Jos A.; Pilz, Stefan; Loerbroks, Adrian; Kleber, Marcus E.; Grammer, Tanja B.; Böhm, Bernhard O.; März, Winfried (Clinical endocrinology, 2013)
Objective Evidence suggests that vitamin D may protect against the onset of diabetes. However, the mechanisms underlying the role of vitamin D on glycaemic status are unclear and warrant further investigation. We sought to determine the relationship between serum 25-hydroxyvitamin D (25[OH]D) and glycaemic status among intermediate-to-high-risk patients scheduled for coronary angiography. Methods Participants were 3316 male and female patients (mean ± SD age, 62·7 ± 10·6 years). Four categories were formed according to serum 25[OH]D levels. The association between serum 25[OH]D and diabetes was assessed using multivariable logistic regression. Results Fasting and 2 h post-load glucose, HbA1c and the HOMA-IR indices diminished with increasing serum 25[OH]D levels (P < 0·001). However, no associations were observed between insulin, pro-insulin or C-peptide and serum 25[OH]D concentrations. The pro-inflammatory markers IL-6 and hs-CRP also decreased considerably with higher vitamin D levels (P < 0·001). After full adjustment, those with optimal serum 25[OH]D levels had a reduced odds for fasting diabetes (OR = 0·63; 95% CI, 0·46-0·86; Ptrend = 0·01), 2 h post-load diabetes (OR = 0·46; 95% CI, 0·29-0·74; Ptrend = 0·004), both fasting/2 h post-load diabetes (OR = 0·61; 95% CI, 0·42-0·87; Ptrend = 0·001) and all of the combined hyperglycaemic states (OR = 0·68; 95% CI, 0·52-0·80; Ptrend = 0·01). Conclusions Higher serum 25[OH]D levels were associated with better glycaemic status and lower inflammation. Should these observations be confirmed in future studies, vitamin D supplementation may prove a useful adjunct in attenuating the onset of diabetes.
Gesehen am 31.03.2022